The auxin-like effect of substrate and auxin sensitivity of plant modulate the PGPR activity of Lysinibacillus pinottii sp. nov. PB211 - Manuel Pantoja-Guerra; Nelson Valero-Valero; Camilo A. Ramirez (Chemical and Biological Technologies in Agriculture)
Abstract Background Bacterial auxin production is a mechanism that promotes plant growth. However, it can also be linked to deleterious rhizobacteria and plant-pathogenic bacteria. High levels of auxins have the potential to impede plant growth. Additionally, certain environmental factors can enhance auxin activity and impact the activity of plant growth-promoting rhizobacteria (PGPR). Results In this work, we boarded how the auxin-like effect in the soil–plant system modulates the plant growth-promoting activity of Lysinibacillus pinottii sp. nov. PB211. The effect of humified organic matter (HOM) soil was simulated with humic acids (HA) coming from vermicompost; the spectral configuration (13C-CP-TOSS-NMR and FTIR) and coleoptile elongation test indicated its bioactivity. Cucumber exhibits a PGP effect of PB211 and HA at a lower concentration compared to corn. This disparity agrees with the differential sensitivity to auxins of both plant models. Monocot plants, such as corn, generally exhibit greater resistance to exogenous auxin activity compared to eudicot plants, such as cucumber. The presence of HA in the growth substrate (sand) is found to modulate the PGPR activity of PB211, resulting in a loss of PGPR activity. Conclusions The findings highlight the importance of considering the cumulative auxin-like effects in the soil–plant system when utilizing bacterial inoculants for plant growth promotion in agriculture. Graphical Abstract